Lost and Found: Coffea stenophylla and C. affinis, the Forgotten Coffee Crop Species of West Africa - Davis, Aaron P.; Gargiulo, Roberta; Fay, Michael F.; Sarmu, Daniel; Haggar, Jeremy (Frontiers in Plant Science, 2020)
Coffea arabica (Arabica) and C. canephora (robusta) almost entirely dominate global coffee production. Various challenges at the production (farm) level, including the increasing prevalence and severity of disease and pests and climate change, indicate that the coffee crop portfolio needs to be substantially diversified in order to ensure resilience and sustainability. In this study, we use a multidisciplinary approach (herbarium and literature review, fieldwork and DNA sequencing) to elucidate the identity, whereabouts, and potential attributes, of two poorly known coffee crop species: C. affinis and C. stenophylla. We show that despite widespread (albeit small-scale) use as a coffee crop species across Upper West Africa and further afield more than 100 years ago, these species are now extremely rare in the wild and are not being farmed. Fieldwork enabled us to rediscover C. stenophylla in Sierra Leone, which previously had not been recorded in the wild there since 1954. We confirm that C. stenophylla is an indigenous species in Guinea, Sierra Leone, and Ivory Coast. Coffea affinis was discovered in the wild in Sierra Leone for the first time, having previously been found only in Guinea and Ivory Coast. Prior to our rediscovery, C. affinis was last seen in the wild in 1941, although sampling of an unidentified herbarium specimen reveals that it was collected in Guinea-Conakry in 2015. DNA sequencing using plastid and ITS markers was used to: (1) confirm the identity of museum and field collected samples of C. stenophylla; (2) identify new accessions of C. affinis; (3) refute hybrid status for C. affinis; (4) identify accessions confused with C. affinis; (5) show that C. affinis and C. stenophylla are closely related, and possibly a single species; (6) substantiate the hybrid C. stenophylla × C. liberica; (7) demonstrate the use of plastid and nuclear markers as a simple means of identifying F1 and early-generation interspecific hybrids in Coffea; (8) infer that C. liberica is not monophyletic; and (9) show that hybridization is possible across all the major groups of key Africa Coffea species (Coffee Crop Wild Relative Priority Groups I and II). Coffea affinis and C. stenophylla may possess useful traits for coffee crop plant development, including taste differentiation, disease resistance, and climate resilience. These attributes would be best accessed via breeding programs, although the species may have niche-market potential via minimal domestication.